2020
DOI: 10.2169/internalmedicine.5394-20
|View full text |Cite
|
Sign up to set email alerts
|

A Favipiravir-induced Fever in a Patient with COVID-19

Abstract: We herein report the first case of a fever induced by favipiravir, a potential coronavirus disease 2019 therapeutic drug. An 82-year-old man diagnosed with bilateral pneumonia was transferred to our hospital following a positive severe acute respiratory syndrome coronavirus 2 polymerase chain reaction test. He was treated with compassionate use of favipiravir. Both his oxygen demand and fever gradually improved after admission; however, his fever relapsed, and the C-reactive protein (CRP) levels increased on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…8 Besides, a case report of favipiravir-related cholestatic liver injury was recently presented by Yamazaki et al. 5 In our case, acute liver injury (ALI) developed right after the initiation of Favipiravir treatment in a patient with normal liver function test at baseline. Discontinuation of favipiravir along with steroid therapy for toxic hepatitis resulted in rapid improvement in liver function tests.…”
Section: Discussionmentioning
confidence: 56%
“…8 Besides, a case report of favipiravir-related cholestatic liver injury was recently presented by Yamazaki et al. 5 In our case, acute liver injury (ALI) developed right after the initiation of Favipiravir treatment in a patient with normal liver function test at baseline. Discontinuation of favipiravir along with steroid therapy for toxic hepatitis resulted in rapid improvement in liver function tests.…”
Section: Discussionmentioning
confidence: 56%
“…After favipiravir administration, the clinical status improved in 74 cases, worsened in 48 cases (with 21 deaths), and was unclear in 20 cases. The reported side effects were hyperuricemia Hosoba et al, 2020;Ono et al, 2020;Takoi et al, 2020 ), fever ( Koba et al, 2020 ;Kurita et al, 2020 ;Takoi et al, 2020 ), lymphocytosis ( Dauby et al, 2021 ), eosinophilia ( Takoi et al, 2020 ), lymphocytopenia ( Atallah et al, 2020 ), hepatotoxicity ( Hosoba et al, 2020 ;Takumida et al, 2021 ;Yamazaki et al, 2021 ), nephrotoxicity ( Nasa et al, 2021 ), acute pancreatitis ( Khan et al, 2021 ), wood's lamp fluorescence on nails and hair, and nausea ( Aslan Kayiran et al, 2021 ).…”
Section: Case Reportsmentioning
confidence: 99%
“…However, as in our case, drug fever after 10 days of favipiravir was described in a case report by Takoi and his colleagues ( Takoi et al, 2020 ). Also, Kurita et al reported that the favipiravir-induced drug fever occurred about a week after administration ( Kurita et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%